ANALISIS RISIKO CURAH HUJAN TINGGI TERHADAP KELANGSUNGAN KEGIATAN BELAJAR DAN MENGAJAR DI MTS HUDATUL FALAH - Muhamad Fathi; Wahyu Hidayat (AKSI: Jurnal Manajemen Pendidikan Islam, 2023)
Heavy rainfall can have a significant impact on the smoothness of teaching and learning activities in schools. The research findings indicate that high rainfall disrupts the punctuality of students and teachers in attending school due to poor weather conditions. Student and teacher lateness and absences affect the smoothness of the learning process at MTs Hudatul Falah. Additionally, certain parts of the school building have also been damaged due high rainfall, such as roofs, walls and stairs. The school has taken measures to address the impact of high rainfall, including improving the maintenance and repair of the school building, as allowing tolerance for lateness and providing flexibility in the class schedule. Evaluations of the school's readiness and the empowerment of teachers and students in dealing with emergencies related to high rainfall have also been conducted. This research provides insights into the importance of addressing the impact of extreme weather conditions in the educational context. The impact of high rainfall, particularly student and teacher lateness, requires greater attention to improving the condition of school buildings and increasing readiness to face the risks of extreme weather. These steps will help ensure the continuity of teaching and learning activities in the future.